Assessing communication strategies in argumentation-based negotiation agents equipped with belief revision - Casali, Ana (2016)
The importance of negotiation has increased in the last years as a relevant interaction to solve conflicts in multiagent systems. Although there are many different scenarios, a typical negotiating situation involves two cooperative agents that cannot reach their goals by themselves because they do not have some resources needed to reach such goals. Therefore, a way to improve their mutual benefit is to start a negotiation dialogue, taking into account that they might have incomplete or incorrect beliefs about the other agent´s goals and resources. The exchange of arguments during the negotiation gives them information that makes it possible to update their beliefs and consequently they can offer proposals which are closer for reaching a deal. In order to formalize their proposals in a negotiation setting, the agents must be able to generate, select and evaluate arguments associated with such offers, updating their mental state accordingly. We situate our work on this kind of scenarios with two argumentation-based negotiation agents equipped with belief revision operations in the generation and interpretation of arguments. It has been proved that those agents that take advantage of belief revision during the negotiation achieve an overall better performance. Because the belief revision process depends on the information the agents exchange in their utterances, in this paper we focus on different communication strategies the agents may implement and the impact that they have in the negotiation process. For this purpose, we present a negotiation protocol where the messages are extended to include a critique to the last proposal received and a counterproposal. Also, we define proposals that may be more or less informative containing different justifications. An intentional agent architecture is proposed and following this model different kind of negotiating agents are created using diverse communication strategies. To assess the impact these strategies have in the negotiation process some simulations are conducted, analyzing the results obtained.